Metabolic effects of initiating lopinavir/ritonavir-based regimens among young children. (23rd October 2018) - Patel, Kunjal; Lindsey, Jane; Angelidou, Konstantia; Aldrovandi, Grace; Palumbo, Paul
Abstract : Objective: The aim of this study was to estimate the long-term metabolic effects of initiating a lopinavir/ritonavir (LPV/r)-based regimen as a first-line therapy for HIV-infected children less than 3 years of age in resource-limited settings. Design: A prospective cohort study after conclusion of the P1060 randomized clinical trials (ClinicalTrials.gov Identifier: NCT00307151), with an overall follow-up of 7 years. Methods: Longitudinal total cholesterol and triglyceride measures were compared between 222 and 227 children randomized to initiate LPV/r and nevirapine (NVP)-based regimens, respectively. Adipokines (adiponectin and leptin) and biomarkers of inflammation [C-reactive protein and interleukin (IL)-6], microbial translocation (lipopolysaccharide) and immune activation (sCD14), measured in 117 participants at a median of 45 weeks of follow-up, were also compared by a randomized arm. Results: Mean total cholesterol and the percentage of participants with borderline or high total cholesterol was higher in the LPV/r arm from years 3 to 7 of follow-up than in the NVP arm (adjusted relative differences ranging from 10.9 to 23.4 mg/dl and adjusted relative risks ranging from a 60% increased risk to a more than four-fold increased risk for cholesterol ≥170 mg/dl at 7 years of follow-up). Initiation of a LPV/r-based regimen was not associated with high triglycerides over follow-up or large differences in markers of metabolic syndrome, inflammation, microbial translocation or immune activation. Conclusion: Given the virologic superiority of LPV/r-based regimens in young children and open questions regarding the roll-out of dolutegravir in resource-limited settings, children are currently being maintained on LPV/r-based regimens. Our results suggest continual assessment of total cholesterol among young children initiating a LPV/r-based regimen to monitor cardiometabolic health. Abstract : Supplemental Digital Content is available in the text